Online peer assessment: helping to facilitate learning through participation - Jamie Cleland; Geoff Walton (Journal of Learning Development in Higher Education, 2012)
The focus of this paper is on the combination of enquiry-based learning, information literacy and e-learning and how they are embedded in an online peer assessment exercise. What it shall present is a structure and strategy that aids student learning in the short and long-term. Ninety eight students completed a questionnaire before and after a three-week online peer assessment exercise during a first year undergraduate research and study skills module. The results demonstrate that a significant number of students valued the design of the exercise and the benefits it can have on their future learning and development. The paper concludes by suggesting that new and innovative ways of assessment are needed to keep engaging students and develop their learning in different ways.